EXPERIMENTAL DETERMINATION OF THE INFLUENCE OF THE SIZE AND COMPOSITION OF CONTAMINANT PARTICLES ON THE VIBROACOUSTIC CHARACTERISTICS OF MINIATURE BALL BEARINGS ASSEMBLIES - Kostyunik, Ruslan; Mikosianchyk, Oksana; Stelmakh, Oleksandr; Kuschev, Oleksiy; Кovalchuk Olena (Problems of Friction and Wear, 2024)
The influence of lubricant and microgeometric characteristics of surfaces on the vibroacoustic characteristics of miniature rolling bearings is analyzed, and the types of defects that occur in bearings during operation are presented. The method of cleaning the working surfaces of aircraft ball bearings is described. A modernized test and measurement complex has been developed to evaluate the effectiveness of ball bearing cleaning by vibroacoustic parameters. The mechanisms of cleaning aircraft ball bearings by pulsed magnetic-turbulent and ultrasonic methods are determined. It has been established that the magnetic-turbulent method allows more efficient removal of contaminant particles whose size is larger than 1-2 microns, while the average value of the total noise level of bearings of series No. 5-1000901T2 - decreased by 4 dB, and of series No. 75-70001016T2 - decreased by 1.2 dB, while the use of the ultrasonic method allowed to reduce the total noise level by 0.67 dB and 0.49 dB, respectively. However, the ultrasonic cleaning method showed the highest efficiency for the smallest contaminants. It has been established that the presence of microparticles whose size is much larger than 1-2 microns leads to an increase in vibration acceleration in the low-frequency measurement range. As shown by the study, cleaning of microbearings on the ОPSH-01 stand is the most effective method of removing bulk contaminants, which reduces the overall noise level by 1.2...4 dB. The presence of a more significant number of microparticles of contaminants with a size of 1-2 microns leads to an increase in vibration acceleration by 2.5...30 % in the high-frequency measurement range. For the removal of this type of particles, the highest efficiency has been achieved by the ultrasonic method, the cleaning of which reduces the overall noise level by 0.49...0.67 dB.